2019
DOI: 10.3390/ijgi8030139
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic Land Cover Mapping of Urbanized Cities with Landsat 8 Multi-temporal Images: Comparative Evaluation of Classification Algorithms and Dimension Reduction Methods

Abstract: Uncontrolled and continuous urbanization is an important problem in the metropolitan cities of developing countries. Urbanization progress that occurs due to population expansion and migration results in important changes in the land cover characteristics of a city. These changes mostly affect natural habitats and the ecosystem in a negative manner. Hence, urbanization-related changes should be monitored regularly, and land cover maps should be updated to reflect the current situation. This research presents a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 62 publications
0
6
0
Order By: Relevance
“…The resultant maps from these processes rapidly become outmoded with the passage of time due the dynamic changes occurring in the world. Remote Sensing techniques on the other hand provides accurate LULC maps and monitoring changes at relatively less labour intensive, regular intervals of time and can be continuously updated (Mani and Varghese 2018;Alganci 2019). Despite the spatial and spectral heterogeneity challenges of agricultural lands (tree cash crops like cocoa, palm, oranges to perennial crops such as maize, rice, plantain) in Africa and urban environments, remote sensing remains the preferred choice as the suitable source of reliable information about the multiple facets of LULC (Pandey et al 2019;Orynbaikyzy et al 2019).…”
Section: Discussion Remote Sensing and Gis In Lulc Appraisalmentioning
confidence: 99%
“…The resultant maps from these processes rapidly become outmoded with the passage of time due the dynamic changes occurring in the world. Remote Sensing techniques on the other hand provides accurate LULC maps and monitoring changes at relatively less labour intensive, regular intervals of time and can be continuously updated (Mani and Varghese 2018;Alganci 2019). Despite the spatial and spectral heterogeneity challenges of agricultural lands (tree cash crops like cocoa, palm, oranges to perennial crops such as maize, rice, plantain) in Africa and urban environments, remote sensing remains the preferred choice as the suitable source of reliable information about the multiple facets of LULC (Pandey et al 2019;Orynbaikyzy et al 2019).…”
Section: Discussion Remote Sensing and Gis In Lulc Appraisalmentioning
confidence: 99%
“…These parameters include: (i) generic parameters of the algorithm (Gamma parameter and The penalty parameter) and (ii) software specific parameters of the classification process (Pyramid levels, Pyramid reclassification threshold, and Classification probability threshold). In their works, Alganci, 2019, Petropoulos et al, 2010, Petropoulos et al, 2011, and Srivastava et al, 2012 described the use of the suitable values for these parameters when using SVM. Gamma parameter is calculated as the inverse of the number of image bands.…”
Section: Producing Lulc Of Quseir 2421 Svm For Lulc Classificationmentioning
confidence: 99%
“…To better understand ecological patterns, it is also expanded to the species-level mapping of vegetation [19]. Other research, like References [20,21], presented a comparative evaluation of the pixel-based method and the object-based; especially, Reference [21] compared the pixel-based support vector machine (SVM) classification and decision-tree-oriented geographic object-based image analysis (GEOBIA) classification, which indicated that the GEOBIA classification provided the highest accuracy. Besides, work, like Reference [22], discussed the idea and method of geographic ontology modeling based on object-oriented remote sensing technology in detail.…”
Section: Related Workmentioning
confidence: 99%